Beyond brokering: Sourcing agents, boundary work and working conditions in global supply chains. (April 2018) - Soundararajan, Vivek; Khan, Zaheer; Tarba, Shlomo Yedidia
The role that sourcing agents, autonomous peripheral actors located in developing economies, play in the governance of working conditions in global supply chains has been greatly underexplored in the literature. The present article reports on an in-depth qualitative study of garment supply chains that examined the boundary work of Indian sourcing agents aimed at dismantling or bridging the boundaries that affect the interaction between western buyers and local suppliers, in order to facilitate development and implementation of meaningful working conditions or social relations at work. We identify four types of boundary work that sourcing agents used to manage combinations of accommodative and non-accommodative buyers and suppliers in order to work through boundaries created by buyers' liability of foreignness: reinforcing, flexing (type 1 and 2) and restoring. We also found four essential conditions for a sourcing agent to become an effective boundary spanner in practice: acquiring knowledge about the relevant fields and actors, gaining legitimacy in the relevant fields and in the opinion of the parties involved, effectively translating the expectations of each party to the other, and benefiting from satisfying incentives. We contribute to the literature on governance for working conditions in global supply chains, boundary theory and liability of foreignness.